Properties of glass-ceramics obtained from crystallization of the SiO2-Al2O3-MgO-Li2O system with addition of ZrO2 - Souza Filho, Manoel Pereira de [UNESP]; Campos, Elson de [UNESP]; Moreira, Janaina Pardi; Lopes, Cristina Moniz Araujo; Melo, Francisco Cristóvão Lourenço de (Trans Tech Publications Ltd, 2014)
This paper presents the study results with glass-ceramics obtained from base glass (MgO-Al2O3- SiO2-Li2O system) with addition of ZrO2 as nucleating agent. The glass was melted at 1650 degrees C for 3 h and at a heating rate of 10 degrees C/min. The molten glass was poured into a graphite mold to obtain monolithic samples and also in water in order to obtain particulate material. Such material was grinded and then pressed by both uniaxial and isostatic pressing methods before being sintered. Both the monolithic and pressed samples were performed under two different conditions of heat treatment so that their nucleation and crystallization occurred. In the first one, the samples were heated to 1100 degrees C with a heating rate of 10 degrees C/min. In the second one, there was an initial heating rate of 10 degrees C/min up to 780 degrees C, which was kept for 5 minutes. After that, the samples were heated to 1100 degrees C at a heating rate of 1 degrees C/min. Microhardness analyses showed that base glass presented values around 7.0 GPa. The glass-ceramics obtained from the powder sintering showed microhardness values lower than those obtained from monolithic samples. The highest hardness values were observed in the samples which were treated with two heating rates, whose values were around 9.2 +/- 0.5 GPa. Moreover, the glass-ceramics which were produced with an only heating rate, presented values around 7.1 +/- 0.2 GPa, very close to those observed in the base glass.
Keywords: Glass-ceramics; Hardness; Glass; SiO2-Al2O3-MgO-Li2O system